Muḥammad ‘Ābid al-Jābirī’s Thoughts on Tradition and Modernity in Renewal - Yunita Novia (Program Doktor Akidah dan Filsafat Islam, 2020)
The tradition is something that is present and accompanies contemporary ours, which comes from the past, or could be said of all that is human-related to aspects of thought in Islamic civilization, ranging from the teaching of the doctrinal, shariah, language, literature, art, pen, and sufism. Modern not to break with the past but to upgrade the attitude and stance by assuming the pattern of our relationship with tradition in modern culture. The relation of tradition and modernity, according to al-Jābirī was keeping the good old traditions and take a new tradition better that is, the tradition was reconstructed to internalize the contemporary thoughts. Al-Jābirī strongly emphasized contemporary Arab thoughts (bayani, 'irfani, burhani) as a way to confront modernity. The idea's important contribution is to introduce to us the various constructs reasoning developed in the Islamic world.